Analisa Penerapan Dasar Robotika sebagai Implementasi Pengembangan Robot Sederhana pada Kurikulum Merdeka di SMP Angkasa - Widiadnyana, Putu; Liandana, Made; Gadyanga, I Made Kaluna; Gadyanga, I Komang Dahesa (Indo-MathEdu Intellectuals Journal, 2024)
The application of the Independent Curriculum in informatics subjects, algorithms, and programming materials is a new material taught in Junior High School (SMP). In this subject, there is one material that relates to the manufacture of simple robots. This research aims to implement the basics of robotics to students to stimulate students' interest in learning. This research is quantitative research with an associative approach by implementing an independent learning curriculum that prioritizes generic skills and obstacles faced by students in learning activities. The data collection technique used a questionnaire given to 25 grade VIII students. The questionnaire is used as an evaluation tool and the results of the questionnaire will then be recapped. The results of the analysis showed that students' learning readiness and interest in learning did not have a significant influence on their learning outcomes, while the students' learning profile significantly affected the learning outcomes. The use of learning methods that take into account the individuality of students allows for more personalized and effective learning designs